Pengaruh Tingkat Utang, Ukuran Perusahaan dan Kepemilikan Manajerial pada Persistensi Laba - Dita Arisandi, Ni Nyoman; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence of the effect of debt levels, firm size, and managerial ownership on earnings persistence. This research was conducted at the IDX by selecting samples of property and real estate companies in 2013 to 2016. The number of samples taken was 11 companies with non probability sampling method, namely by purposive sampling. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that the level of debt and managerial ownership had no effect on earnings persistence. Company size has a positive effect on earnings persistence. Large companies have good performance and systems to control, manage, manage all assets owned by the company. This effective and efficient control, management and regulation of company assets has the potential to bring maximum profit. Keywords: Level of debt, firm size, managerial ownership, earnings persistence